Wound Healing in Plastic Surgery: Does Age Matter? An American College of Surgeons National Surgical Quality Improvement Program Study. Issue 3 (March 2015) - Karamanos, Efstathios; Osgood, Geoff; Siddiqui, Aamir; Rubinfeld, Ilan
Abstract : Background: Increasing age has traditionally been associated with impairment in wound healing after operative interventions. This is based mostly on hearsay and anecdotal information. This idea fits with the authors' understanding of biology in older organisms. This dictum has not been rigorously tested in clinical practice. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was retrospectively queried for all patients undergoing plastic surgery from 2005 to 2010. Variables extracted included basic demographics, comorbidities, previous steroid and tobacco use, wound classification at the end of the surgery, and development of postoperative surgical-site infections. Multivariate analyses were used to investigate the impact of aging in wound dehiscence. Results: A total of 25, 967 patients were identified. Overall, the incidence of wound dehiscence was 0.75 percent ( n = 196). When patients younger than 30 years were compared to older patient groups, no difference in the probability of developing wound dehiscence was noted. Specifically, the groups of patients aged 61 to 70 years and older than 70 years did not have statistically significant wound healing deficiencies [adjusted OR, 0.63 (95 percent CI, 0.11 to 3.63), adjusted p = 0.609; 2.79 (0.55 to 14.18), adjusted p = 0.217, for 61 to 70 years and older than 70 years, respectively]. Factors independently associated with wound dehiscence included postoperative abscess development, paraplegia, quadriplegia, steroid and tobacco use, deep surgical-site infection development, increasing body mass index, and wound classification at the end of surgery. Conclusions: In patients undergoing plastic surgery, wound dehiscence is a rare complication (0.75 percent). Aging is not associated with an increased incidence of wound dehiscence. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.